Psoriasis Does Not Seem to Impair Glomerular and Tubular Function – The Comprehensive Study on Serum and Urine - Nowowiejska J; Baran A; Hermanowicz JM; Sieklucka B; Koper-Lenkiewicz OM; Kamińska J; Pawlak K; Pawlak D; Flisiak I (Psoriasis: Targets and Therapy)
Julia Nowowiejska,1 Anna Baran,1 Justyna Magdalena Hermanowicz,2 Beata Sieklucka,3 Olga Martyna Koper-Lenkiewicz,4 Joanna Kamińska,4 Krystyna Pawlak,3 Dariusz Pawlak,2 Iwona Flisiak1 1Department of Dermatology and Venereology, Medical University of Bialystok, Bialystok, Poland; 2Department of Pharmacodynamics, Medical University of Bialystok, Bialystok, Poland; 3Department of Monitored Pharmacotherapy, Medical University of Bialystok, Bialystok, Poland; 4Department of Clinical Laboratory Diagnostics, Medical University of Bialystok, Bialystok, PolandCorrespondence: Julia Nowowiejska, Department of Dermatology and Venereology, Medical University of Bialystok, Zurawia 14 St., 15-540, Bialystok, Poland, Email julia.nowowiejska@umb.edu.plIntroduction: There is a dispute as to whether patients with psoriasis have impaired kidney function. We aimed to assess several recognized and experimental markers of glomerular filtration and tubular function in such patients to find out whether they have decreased kidney function.Methods: The study involved 60 patients with psoriasis and 30 volunteers without dermatoses. The following molecules were analyzed by ELISA: serum creatinine, cystatin C, beta-trace protein, albumins, uromodulin; urinary albumins, cystatin C, alpha-1-microglobulin, beta-2-microglobulin, uromodulin, klotho, and fatty acid-binding protein 1, and nephrin.Results: The following absolute values of markers concentrations were measured in patients, respectively: serum-1.13 (0.6– 1.9)mg/dl, 4.511 (2.356– 10.31)mg/l, 19.8 (2.8– 48)ng/mL, 4.2 (1.9– 8.85)g/dl, 212.3 (32.35– 583.9)ng/mL, urine– 5 (3– 39)g/dl, 24096 (79.94– 99020)ng/mL, 0.9342 (0.2088– 6.213)ng/mL, 22.65 (0.85– 105.8)ng/mL, 6.388 (0.8960– 15.94)ng/mL, 0.08 (0.002– 0.387)ng/mL, 1.773 (1.706– 2.146)ng/mL, 0.128 (0.095– 0.298)ng/mL. The patients had significantly lower serum albumin concentration (p< 0.001) and higher urinary albumin (p< 0.05), significantly higher serum cystatin C (p< 0.01), and absolute urinary nephrin (p< 0.05). There was no difference between patients and controls in terms of serum creatinine or beta trace protein concentration (p> 0.05). There were no significant differences in the concentration of the tubular markers (urinary cystatin C, alpha-1-microglobulin, beta-2-microglobulin, klotho, and fatty acid-binding protein 1) between patients and controls, except for serum and urinary uromodulin, which were significantly lower in patients (p< 0.01, p< 0.001, respectively). We found no significant correlations between the investigated markers’ concentration and clinical or demographic parameters (p> 0.05).Discussion: Despite the differences between patients and controls in terms of glomerular filtration markers, the median values of markers’ concentration were within normal limits. Based on the assessment of the markers, it does not seem that impaired glomerular and tubular function occurs more frequently in patients with psoriasis. Nevertheless, due to the higher prevalence of diabetes mellitus and arterial hypertension in psoriatics and nephrotoxic properties of antipsoriatic drugs – caution must be exercised and easy screening tools should be considered.Keywords: psoriasis, glomerular function, tubular function, creatinine, albumin, cystatin C, uromodulin, fatty acid-binding protein 1